The transformation of Perak’s political and economic structure in the British Colonial period in Malaya (1874-1957) - Azrai Abdullah,; Izdihar Baharin,; Rizal Yaakop, (Penerbit UKM, 2012)
This paper analyses the political economy of the state of Perak under colonial rule. It explores how Perak experienced a tremendous transformation in her political and economic structure, one that paved the way for modernization and rapid economic progress. This development was the direct result of Britain’s colonial government involvement in Perak’s administration. Their intervention broke down many traditional barriers that had long confined Perak’s economy to a state of self-reliance, and also managed to integrate her economy with international trends by encouraging foreign investment and utilising cheap labour. These changes brought in new technologies and infrastructure that set the stage for Perak to become one of the most progressive states in Malaya’s post-independence history